Development and validation of a numerical model for an inflatable paper dunnage bag using finite element methods - Venter, Martin Philip (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2011.